2022
DOI: 10.1098/rstb.2021.0339
|View full text |Cite
|
Sign up to set email alerts
|

What would have happened? Counterfactuals, hypotheticals and causal judgements

Tobias Gerstenberg

Abstract: How do people make causal judgements? In this paper, I show that counterfactual simulations are necessary for explaining causal judgements about events, and that hypotheticals do not suffice. In two experiments, participants viewed video clips of dynamic interactions between billiard balls. In Experiment 1, participants either made hypothetical judgements about whether ball B would go through the gate if ball A were not present in the scene, or counterfactual judgements about whether ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…For prediction, one only needs to unroll a simulation of what will happen forward. Giving causal explanations, however, involves a comparison of what actually happened with what would have happened otherwise (Gerstenberg, in press).…”
Section: People’s Intuitive Understanding Of the Physical Worldmentioning
confidence: 99%
See 2 more Smart Citations
“…For prediction, one only needs to unroll a simulation of what will happen forward. Giving causal explanations, however, involves a comparison of what actually happened with what would have happened otherwise (Gerstenberg, in press).…”
Section: People’s Intuitive Understanding Of the Physical Worldmentioning
confidence: 99%
“…Gerstenberg et al (2017) showed that people spontaneously engage in counterfactual simulation when making causal judgments as evidenced by their eye movements. People do not just look at what actually happened; they look at where ball B would have gone if ball A had not been present in the scene (see also Gerstenberg, in press).…”
Section: People’s Intuitive Understanding Of the Physical Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Theories have previously identified that counterfactual simulations in particular may be fundamental to human judgements of causality [87,88], such that people tend to judge that A caused B if and only if B would not have eventuated in the absence of A . As Gerstenberg [89] points out, however, an alternative possibility is that causal judgements depend on hypothetical simulations of the future. That is, people may judge that A caused B by imagining a potential future scenario in which A is absent and B therefore fails to eventuate.…”
Section: Ultimate Questions: Functions and Phylogenymentioning
confidence: 99%
“…During CFR, mental representations that are explicitly contrary to facts or beliefs are imagined (Roese & Morrison, 2009). More precise definitions focus on mentally travelling back in time to observe something that actually happened and imagining a change to what actually happened by simulating how this alternatively would have turned out differently (Beck, Riggs, & Burns, 2011;Gerstenberg, 2022;Rafetseder et al, 2013). The question of whether children can reason counterfactually and what types of thinking count as true CFR is frequently debated in the developmental literature (Beck, Riggs, & Burns, 2011;Nyhout & Ganea, 2019a;Rafetseder et al, 2013;Rafetseder & Perner, 2010.…”
Section: The Cognitive Mechanisms Of Counterfactual Reasoningmentioning
confidence: 99%